Editorial Page - Alam, AHM Zahirul (IIUM Engineering Journal, 2019)
CHIEF EDITOR Ahmad Faris Ismail, IIUM, Malaysia EXECUTIVE EDITOR AHM Zahirul Alam, IIUM, Malaysia ASSOCIATE EDITOR Anis Nurashikin Nordin, IIUM, Malaysia LANGUAGE EDITOR Lynn Mason, Malaysia COPY EDITOR Hamzah Mohd. Salleh, IIUM, Malaysia EDITORIAL BOARD MEMBERS Abdullah Al-Mamun, IIUM, Malaysia Abdumalik Rakhimov, IIUM, Malaysia Amir Akramin Shafie, IIUM, Malaysia Erry Yulian Triblas Adesta, IIUM, Malaysia Erwin Sulaeman, IIUM, Malaysia Hanafy Omar, Saudi Arabia Hazleen Anuar, IIUM, Malaysia Konstantin Khanin, University of Toronto, Canada Ma’an Al-Khatib, IIUM, Malaysia Md Zahangir Alam, IIUM, Malaysia Meftah Hrairi, IIUM, Malaysia Mohamed B. Trabia, United States Mohammad S. Alam, Texas A&M University-Kingsville, United States Muataz Hazza Faizi Al Hazza, IIUM, Malaysia Mustafizur Rahman, National University Singapore, Singapore Nor Farahidah Binti Za’bah, IIUM, Malaysia Ossama Abdulkhalik, Michigan Technological University, United States Rosminazuin AB. Rahim, IIUM, Malaysia Waqar Asrar, IIUM, Malaysia INTERNATIONAL ADVISORY COMMITTEE Anwar, United States Abdul Latif Bin Ahmad, Malaysia Farzad Ismail, USM, Pulau Pinang, Malaysia Hanafy Omar, Saudi Arabia Hany Ammar, United States Idris Mohammed Bugaje, Nigeria K.B. Ramachandran, India Kunzu Abdella, Canada Luis Le Moyne, ISAT, University of Burgundy, France M Mujtaba, United Kingdom Mohamed AI-Rubei, Ireland Mohamed B Trabia, United States Mohammad S. Alam, Texas A&M University-Kingsville, United States Nazmul Karim Ossama Abdulkhalik, Michigan Technological University, United States Razi Nalim, IUPUI, Indianapolis, Indiana, United States Syed Kamrul Islam, United States Tibor Czigany, Budapest University of Technology and Economics, Hungary Yiu-Wing Mai, The University of Sydney, Australia. AIMS & SCOPE OF IIUMENGINEERING JOURNAL The IIUM Engineering Journal, published biannually, is a carefully refereed international publication of International Islamic University Malaysia (IIUM). Contributions of high technical merit within the span of engineering disciplines; covering the main areas of engineering: Electrical and Computer Engineering; Mechanical and Manufacturing Engineering; Automation and Mechatronics Engineering; Material and Chemical Engineering; Environmental and Civil Engineering; Biotechnology and Bioengineering; Engineering Mathematics and Physics; and Computer Science and Information Technology are considered for publication in this journal. Contributions from other areas of Engineering and Applied Science are also welcomed. The IIUM Engineering Journal publishes contributions under Regular papers, Invited review papers, Short communications, Technical notes, and Letters to the editor (with publication charge). REFEREES’ NETWORK All papers submitted to IIUM Engineering Journal will be subjected to a rigorous reviewing process through a worldwide network of specialized and competent referees. Each accepted paper should have at least two positive referees’ assessments. SUBMISSION OF A MANUSCRIPT A manuscript should be submitted online to the IIUM-Engineering Journal website: https://journals.iium.edu.my/ejournal. Further correspondence on the status of the paper could be done through the journal website and the e-mail addresses of the Executive Editor: zahirulalam@iium.edu.my Faculty of Engineering, International Islamic University Malaysia (IIUM), Jan Gombak, 53100, Kuala Lumpur, Malaysia. Phone: (603) 6196 4529, Fax:(603) 6196 4488. Published by International Islamic University Malaysia Jalan Gombak, 53100 Kuala Lumpur, Malaysia Phone (+603) 6196-5018, Fax: (+603) 6196-6298 Website: http://www.iium.edu.my/office/iiumpress Whilst every effort is made by the publisher and editorial board to see that no inaccurate or misleading data, opinion or statement appears in this Journal, they wish to make it clear that the data and opinions appearing in the articles and advertisement herein are the responsibility of the contributor or advertiser concerned. Accordingly, the publisher and the editorial committee accept no liability whatsoever for the consequence of any such inaccurate or misleading data, opinion or statement. IIUM ENGINEERING JOURNAL ISSN: 1511-788X E-ISSN: 2289-7860 Volume 20, Issue 1, June 2019 Table of Content Editorial Page COVER PAGE CHEMICAL AND BIOTECHNOLOGY ENGINEERING COMPARATIVE METAGENOMICS ANALYSIS OF PALM OIL MILL EFFLUENT (POME) USING THREE DIFFERENT BIOINFORMATICS PIPELINES Adibah parmen, MOHD NOOR MAT ISA, FARAH FADWA BENBELGACEM, Hamzah Mohd Salleh, Ibrahim Ali Noorbatcha 1 - 11 PDF LIPASE IMMOBILIZATION ON FIBERS GRAFTED WITH POLYGLYCIDYL METHACHRYLATE Maan Alkhatib, Nik Adlin Bahrudin, HAMZAH M. SALLEH, Teo M. Ting 12 - 23 PDF COLONY COMPOSITION AND BIOMASS OF MACROTERMES GILVUS HAGEN (BLATTODEA: TERMITIDAE) IN INDONESIA NIKEN SUBEKTI, Priyantini Widiyaningrum, Dodi Nandika, Dedy Duryadi Solihin 24 - 28 PDF CIVIL AND ENVIRONMENTAL ENGINEERING A SURVEY OF MATLAB EFFICIENCY IN DAMAGE DETECTION OF CONCRETE GRAVITY IN CONCRETE GRAVITY DAMS Sajad Esmaielzadeh, Hassan Ahmadi, Seyed Abbas Hosseini 29 - 48 PDF IMPLEMENTATION OF GOVERNMENT ASSET MANAGEMENT USING TERRESTRIAL LASER SCANNER (TLS) AS PART OF BUILDING INFORMATION MODELLING (BIM) Asep Yusup Saptari, S. Hendriatiningsih, Dony Bagaskara, Levana Apriani 49 - 69 PDF THE ANALYSIS OF LIQUEFACTION PHENOMENON OF THE FLEXIBLE PAVEMENT USING SEISMIC MONITORING EQUIPMENT RINI KUSUMAWARDANI, Untoro Nugroho, Sri Handayani, Mareta Aspirilia Fananda 70 - 78 PDF ELECTRICAL, COMPUTER AND COMMUNICATIONS ENGINEERING PSG DYNAMIC CHANGES IN METHAMPHETAMINE ABUSE USING RECURRENCE QUANTIFICATION ANALYSIS Sayyed Majid Mazinani, GHASEM SADEGHI BAJESTANI 79 - 89 PDF FINITE ELEMENT SIMULATION OF MEMS PIEZOELECTRIC ENERGY SCAVENGER BASED ON PZT THIN FILM Aliza Aini Md Ralib, Nur Wafa Asyiqin Zulfakher, Rosminazuin Ab Rahim, Nor Farahidah Za’bah, Noor Hazrin Hany Mohamad Hanif 90 - 99 PDF Evaluation on the Effectiveness of Visual Learning Environment on Programming Course From Students’ Perspectives Nasa Zata Dina, Eto Wuryanto, Rachman Sinatriya Marjianto 100 - 107 PDF TOWARDS AN EFFICIENT TRAFFIC CONGESTION PREDICTION METHOD BASED ON NEURAL NETWORKS AND BIG GPS DATA Wiam Elleuch, Ali Wali, Adel M. Alimi 108 - 118 PDF AUGMENTATIVE AND ALTERNATIVE COMMUNICATION METHOD BASED ON TONGUE CLICKING FOR MUTE DISABILITIES NIK NUR WAHIDAH NIK HASHIM, MUHAMMAD AMIRUL AMIN AZMI, HAZLINA MD. YUSOF 119 - 128 PDF A COMBINED DEEP LEARNING MODEL FOR PERSIAN SENTIMENT ANALYSIS Zahra Bokaee Nezhad, Mohammad Ali Deihimi 129 - 139 PDF MODIFIED CAPACITOR ASSISTED EXTENDED BOOST QUASI Z-SOURCE INVERTER FOR THE GRID-CONNECTED PV SYSTEM N Hemalatha, Seyezhai Ramalingam 140 - 157 PDF A NOVEL USER PROFILE-BASED FUZZY APPROACH FOR EVALUATING TRUST IN SEMANTIC WEB SOMAYEH ASHTARI, MALIHE DANESH, hossein shirgahi 158 - 176 PDF PLL-BASED 3?; INVERTER CIRCUIT FOR MICROGRID SYSTEM OPERATED BY ELECTROSTATIC GENERATOR S.M.A Motakabber, Tawfikur Rahman, Muhammad I. Ibrahimy, A. H. M. Zahirul Alam 177 - 193 PDF INTELLIGENT CONTROL SYSTEM OF A WHEELCHAIR FOR PEOPLE WITH QUADRIPLEGIA PARALYSIS hayder Fadhil; Saif Hussam; Yasseen Sadoon 194 - 201 PDF MATERIALS AND MANUFACTURING ENGINEERING Adsorptive removal of Pb (II) using exfoliated graphite adsorbent:influence of experimental conditions and magnetic CoFe2O4 decoration Thi Thuong Nguyen, Thi Ngoc Thu Nguyen, Long Giang Bach, Duy Trinh Nguyen, Thi Phuong Quynh Bui 202 - 215 PDF Grease Quality Issues on Middle Voltage Switchgear: Corrosivity, Resistivity, Safety and Ageing Mohd Sabri Mahmud, Sanuri Ishak, Mohd Najib Razali, Mohd Aizudin Abdul Aziz, Musfafikri Musa 216 - 228 PDF MECHANICAL AND AEROSPACE ENGINEERING A RANS K-? SIMULATION OF 2D TURBULENT NATURAL CONVECTION IN AN ENCLOSURE WITH HEATING SOURCES mehdi ahmadi, Seyed Ali Agha Mirjalily, Seyed Amir Abbas Oloomi 240 - 255 PDF MECHATRONICS AND AUTOMATION ENGINEERING MAGNETICALLY INDUCED PIEZOELECTRIC ENERGY HARVESTER VIA HYBRID KINETIC MOTION Huda Azam, Noor Hazrin Hany Mohamad Hanif, Aliza Aini Md Ralib 256 - 268 PDF